Remarks by Maria Flores. (2018) - Flores, Maria
Abstract : I first became involved with international law while I was at university. After graduating, I decided to teach public international law. As an undergraduate, I particularly enjoyed this branch of study. I was attracted to it because it helped me to understand the problems, challenges, and breakthroughs in the field of international relations on a global scale. Therefore, after facing a competitive entry process, I joined the international law department of the Universidad de la República. It was a small department, but the university had produced some well-known scholars like Eduardo Jiménez de Aréchaga, who became a judge at the International Court of Justice, and Hector Gross Espiell, who served as a judge at the Inter-American Court of Human Rights.